Radiographic Value of the Lisfranc Diastasis in a Standardized Population - Thomas, James L; Kopiec, Adam; Mark, Kunkel; Chandler, L Mae (Foot and ankle specialist, 2020)
Injury to the Lisfranc's joint, in particular to the second metatarsal-medial cuneiform (second MMC) joint, can be difficult to evaluate, especially in subtle Lisfranc injuries. The purpose of this study was to determine the value of the Lisfranc joint width (diastasis) of the adult foot in a standardized population thereby establishing a potential reference range when investigating this area for potential injury. The 2nd MMC joint in 50 men and 50 women was evaluated. Individuals with a history of foot/ankle pain, previous foot/ankle operation or fracture, or a history of systemic disease were excluded from the study. Bilateral weightbearing digital anterior-posterior and lateral radiographs were taken using a standardized method. The mean 2nd MMC diastasis in 200 feet was 5.6 mm (95% CI 5.39-5.81). In the female population, the mean 2nd MMC diastasis was 5.8 mm (95% CI 5.51-6.09) as compared with 5.6 mm (95% CI 5.31-5.89) in males. The mean distance between the fifth metatarsal base and first cuneiform in the entire study population was 16.3 mm (95% CI 15.57-17.03). This study helps define baseline measurements of the Lisfranc joint for the general population, which can provide a standard measurement against which suspected foot injuries can be compared. Level IV.